Ex vivo and in vitro antiaging and antioxidant extract activity of the Amelanchier ovalis from Siberia - Asyakina, Lyudmila K.; Atuchin, Victor V.; Drozdova, Margarita; Kozlova, Oksana; Prosekov, Alexander Yu (International journal of molecular sciences)
Phenolic acids are biologically active substances that prevent aging and age-related diseases, e.g., cancer, cardiovascular diseases, Alzheimer’s disease, Parkinson’s disease, etc. Cellular senescence is related to oxidative stress. The Siberian Federal District is rich in medicinal plants whose extracts contain phenolic acids. These plants can serve as raw materials for antiaging, antioxidant food supplements, and Amelanchier ovalis is one of them. In the present research, we tested the phytochemical profile of its extract for phenolic acids. Its geroprotective and antioxidant properties were studied both ex vivo and in vitro using Saccharomyces cerevisiae Y-564 as a model organism. The chromotographic analysis revealed gallic, p-hydroxybenzoic, and protocatechuic acids, as well as derivatives of chlorogenic and gallic acids. The research involved 0.25, 0.5, and 1.0 mg/mL extracts of Amelanchier ovalis, all of which increased the growth and lifespan of yeast cells. In addition, the extracts increased the survival rate of yeast under oxidative stress. An in vitro experiment also demonstrated the antioxidant potential of Amelanchier ovalis against ABTS radicals. Therefore, the Amelanchier ovalis berry extract proved to be an excellent source of phenolic acids and may be recommended as a raw material for use in antioxidant and geroprotective food supplements.